Measuring the Organizational Change Maturity of Chilean Companies - Mac Carte, Pablo; Fariña, Paula (Frontiers in Psychology, 2021)
This research presents the Strategic Change Management (SCM) index, an indicator measuring the level of maturity of organizations to address processes of organizational change. At present, there is no other available indicator that fulfills this function. The index is built with the information provided from an instrument (questionnaire) specially created for this purpose. The instrument was applied to a sample of 151 companies, mostly Chilean. Studies about reliability (Cronbach's α, hierarchical ω coefficients, among others), and instrument validity (second-order confirmatory factor analysis and retrospective validity) are presented. These studies show that the instrument has good psychometric properties. The results show that the degree of maturity of the companies comprising the sample to face change processes is low: 87% of the companies have a basic, initial, or amateur level of maturity; 13% have a professional level; and only one company had an expert level. More validity studies are required; however, the absence of a similar available instrument restrains the realization of more in-depth validity studies at this time.